Comparison Between Numerical and an Experimental Results of Pressure Drop in a Perforated Horizontal Wellbore with a 90° Perforations Phasing - Mustafa, Mohammed A.; Rishack, Qais A.; Abdulwahid, Mohammed A. (Basrah Journal for Engineering Sciences, 2023)
This paper presented experimental and numerical studies to investigate pressure drop in perforation horizontal wellbore with a 90° phasing and 20 spm perforation density. The experimental apparatus has been constructed to calculate the static pressure drop and calculate the exit velocity in the horizontal pipe after mixing the axial flow with the radial flow through the perforations in the wellbore. The specifications of the wellbore used were the inner diameter is 44 mm, length is 2 m, and perforation diameter is 4 mm. For this objective, a simulation model was created in the wellbore using the ANSYS Fluent simulation software by using the standard k-ε model and applied to the (CFD) by changing the axial flow from (40-160) lit/min and constant inflow through perforations from range (0 - 80) lit/min. According to the study’s findings, the increase in the radial flow through the perforations increases the total flow rate ratio and the total pressure drop and vice versa. In addition, an increase in the axial flow mixed with radial flow increases the total pressure drop, friction factor, and a decrease in productivity index. Furthermore, the percentage error of the total pressure drop between the numerical and experimental results in test 4 is about 3.83 %. It was found that the numerical and experimental results represented a good agreement about the study of the flow-through perforations at 90° angle in terms of pressure drop and productivity index, etc.